Does the scholarly communication system satisfy the beliefs and aspirations of new researchers? Summarizing the Harbingers research. Issue 2 (26th December 2019) - Nicholas, David; Watkinson, Anthony; Abrizah, Abdullah; Rodríguez‐Bravo, Blanca; Boukacem‐Zeghmouri, Cherifa; Xu, Jie; Świgoń, Marzena; Herman, Eti
Abstract : A study from the Harbingers research project provides a comprehensive assessment of the main features of the scholarly communications system as viewed by early career researchers (ECRs) in the final year of the study (2018). Aspects covered are: discovery and access, authorship practices, peer review, publishing strategies, open access publishing, open data, sharing, collaboration, social media, metrics, impact, reputation, libraries, publishers, and scholarly transformations. Nearly 120 science and social science researchers from seven countries were questioned about these 16 aspects. It was found that some scholarly features work well for ECRs, and in this category can be included: discovery and access, authorship practices, sharing, collaboration, and publishers. Reputation, publishing strategies, and impact are more problematical, and they, in turn, cause tensions regarding some other factors – social media, open access, and open data. Of the rest, libraries are largely invisible, and ECRs have conflicting views concerning ethical behaviour. Few envisage that transformational change will take place in the next 5 years.